Long run relationship between economic growth, export, population and investment of Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2018)
The objective of this study is to examine the long-run relationship between economic growth, population, export, and investment in Ethiopia using annual data collected from the World development indicator, and FAOSTAT for 18 years from 1990-2007 E.C. Co integration and Granger Causality test. Stationary properties of the data and the order of integration of the data were tested using the Augmented Dickey-Fuller (ADF) test. Variables were non-stationary at levels but stationary in first differences. The long-run effects of Population, export and investment on Economic growth indicated that these variables are positively related to economic growth and statistically significant at 1% level.Int. J. Agril. Res. Innov. & Tech. 8 (2): 61-69, December, 2018